Comparing the COVID-19-related PTSD symptoms between psychiatric patients and healthy subjects: an observational retrospective study from Northern Italy. Issue 5 (28th May 2023) - Caldiroli, A; Tagliabue, I; Turco, M; Capuzzi, E; Fortunato, A; Tringali, A; Montana, C; Maggioni, L; Pellicioli, C; Sibilla, M; Marcatili, M; Crespi, G; et al.
ABSTRACT: COVID-19 pandemic had a great impact on mental health, both in the general population and psychiatric patients. Little is known about the difference between these two populations in perceiving the pandemic as a traumatic event. The aim of the study was to compare psychiatric patients and healthy controls (HC) in terms of change over time of post-traumatic (PTSD) symptoms. Demographic and clinical variables were collected. Impact of Event Scale Revised (IES-R) scores were registered at T1 as lockdown period (March–April 2020) and T2 as restarting (May–June 2020). Descriptive analyses and linear regression models were performed. A total of 166 outpatients and 57 HC were recruited. Time (F = 15.76; p < 0.001) and diagnosis (F = 4.94; p < 0.001) had a significant effect on the change of IES-R scores, which resulted T1 > T2 (p < 0.001), except for subjects affected by Obsessive-Compulsive Disorder (OCD). Overall, IES-R scores were < in patients than in HC (p = 0.02), particularly in the schizophrenia (SKZ) subgroup (p < 0.001). IES-R scores of subjects with personality disorders (PDs) resulted to be > HC, although not statistically significant. The lockdown period was perceived as more traumatic than the reopening phase by both groups, with the exception of OCD patients, probably because of the clinical worsening associated with the urge of control against risks of contamination. Overall, HC reported more PTSD symptoms than psychiatric patients did, particularly SKZ ones. PD patients, in contrast, may be more vulnerable to PTSD symptoms probably as a result of poor coping skills. Together with OCD patients, subjects with PDs may need closer monitoring during the different phases of the pandemic. Trial Registration: ClinicalTrials.gov Identifier: NCT04694482